The Third Wave in Science and Technology Studies Future Research Directions on Expertise and Experience - Caudill, David S.; Conley, Shannon N.; Gorman, Michael E.; Weinel, Martin (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book analyzes future directions in the study of expertise and experience with the aim of engendering more critical discourse on the general discipline of science and technology studies. In 2002, Collins and Evans published an article entitled "The Third Wave of Science Studies," suggesting that the future of science and technology studies would be to engage in "Studies in Expertise and Experience." In their view, scientific expertise in legal and policy settings should reflect a consensus of formally-trained scientists and citizens with experience in the relevant field (but not "ordinary" citizens). The Third Wave has garnered attention in journals and in international workshops, where scholars delivered papers explicating the theoretical foundations and practical applications of the Third Wave. This book arose out of those workshops, and is the next step in the popularization of the Third Wave. The chapters address the novel concept of interactional experts, the useof imitation games, appropriating scientific expertise in law and policy settings, and recent theoretical developments in the Third Wave.